2019
DOI: 10.3390/ma12132125
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Live-Cell Imaging Technology Enables High-Throughput Screening to Verify in Vitro Biocompatibility of 3D Printed Materials

Abstract: With growing advances in three-dimensional (3D) printing technology, the availability and diversity of printing materials has rapidly increased over the last years. 3D printing has quickly become a useful tool for biomedical and various laboratory applications, offering a tremendous potential for efficiently fabricating complex devices in a short period of time. However, there still remains a lack of information regarding the impact of printing materials and post-processing techniques on cell behavior. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Notably and importantly, the biocompatibility of the material used in this study actually renders it a potential candidate for incorporation into a LoC system in for example, biological processes [13,14]. Future studies might seek to validate further modes of μFFE (e.g., isotachophoresis or isoelectric focusing) or to separate further biological samples, such as proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably and importantly, the biocompatibility of the material used in this study actually renders it a potential candidate for incorporation into a LoC system in for example, biological processes [13,14]. Future studies might seek to validate further modes of μFFE (e.g., isotachophoresis or isoelectric focusing) or to separate further biological samples, such as proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The wax can be removed by melting and flushing at ambient temperatures [3,4]. Recently, our group has shown the biocompatibility of the acrylic material following different sterilization procedures for mesenchymal stem cells-a crucial prerequisite if 3D printing is to serve as a serious alternative to lab-on-a-chip (LoC) devices made from PDMS, poly(methyl methacrylate) (PMMA), or glass [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D printing material used in this study is considered to be (in vitro) biocompatible, as has been shown in previous publication [61]. Therefore, the material is suitable for biotechnological applications.…”
Section: Introduction Of Static 3d-printed Flow Cellmentioning
confidence: 93%
“…Therefore, the material is suitable for biotechnological applications. Furthermore, the chemical stability against ethanol or isopropyl alcohol solvents, which are frequently used in the laboratory for material disinfection, was also shown [61]. Since a variety of different 3D printing materials are already commercially available, compatible material with suitable properties can be selected for the most diverse applications and experimental requirements.…”
Section: Introduction Of Static 3d-printed Flow Cellmentioning
confidence: 99%
“…Nowadays, additive manufacturing technology does enable the rapid production of customized labware and high definition experiment-specific equipment—but limitations remain. Even though many 3D printing materials are commercially available, not all of them are suitable for biomedical applications, due to the lack of biocompatibility or sufficient surface properties, for example [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%